2020
DOI: 10.1177/1550059420946648
|View full text |Cite
|
Sign up to set email alerts
|

Development of Frontal EEG Differences Between Eyes-Closed and Eyes-Open Resting Conditions in Children: Data From a Single-Channel Dry-Sensor Portable Device

Abstract: Changes in EEG when moving from an eyes-closed to an eyes-open resting condition result from bottom-up sensory processing and have been referred to as activation. In children, activation is characterized by a global reduction in alpha, frontally present reductions for delta and theta, and a frontal increase for beta. The present study aimed to replicate frontal EEG activation effects using single-channel, dry-sensor EEG, and to extend current understanding by examining developmental change in children. Frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…They [ 10 ] concluded that the study of brain function using devices such as the aforementioned should be encouraged. More recently, Johnstone et al (2020) [ 13 ] replicated the frontal findings of previously reported EEG activation effects in 185 children using a single-channel EEG and, according to the authors, their findings contribute to the validation of the single-channel, dry-sensor, and frontal EEG.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…They [ 10 ] concluded that the study of brain function using devices such as the aforementioned should be encouraged. More recently, Johnstone et al (2020) [ 13 ] replicated the frontal findings of previously reported EEG activation effects in 185 children using a single-channel EEG and, according to the authors, their findings contribute to the validation of the single-channel, dry-sensor, and frontal EEG.…”
Section: Introductionmentioning
confidence: 60%
“…To our knowledge, this is the first study to use a mobile single-channel EEG device to monitor TMo surgeries; for this reason, there is no comparative method. It should be viewed as an exploratory study with highly interesting points that may direct the development of a new device for identifying biological markers to explore surgical stress in oral surgery; NBSKeeg, used in this research, shows fair validity and reliability, and it has been employed by several clinical studies [ 10 11 12 13 23 24 25 26 ]. Clinical modifications of the initial protocol, such as expanding the EEG monitoring period to cover the full surgery and clinically time-controlling the events of the trans-surgical development, could also be an interesting approach.…”
Section: Discussionmentioning
confidence: 99%
“…al. (Johnstone et. al, 2020) reported a developmental increase in frontal alpha power in children from 7 to 12 years old, but no developmental change in beta power.…”
Section: Discussionmentioning
confidence: 99%
“…Barry and colleagues showed that in 8 to 10-year-old children there were signi cant differences in EEG activity from 1.5 to 25 Hz in the EO vs EC conditions using a 19-electrode system (Barry et al, 2009). Johnstone and coauthors recorded EEG with a single electrode device in 7 to 12-year-old participants and similarly found signi cant frontal EO vs EC differences from 0.5 to 25 Hz (Johnstone et al, 2020). Thus, differential responses to the EO vs EC conditions can provide markers of neurobehavioral disorders and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The EEG data were recorded to a PC for processing and quantification, deriving estimates of power in the delta, theta, alpha, and beta EEG bands. Data recorded from this device have been shown to be valid and reliable and show sensitivity to psychological states [ 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%